Eliot's dark angel : intersections of life and art - Schuchard, Ronald (Oxford University Press, 2001)
Schuchard's critical study draws upon previously unpublished and uncollected materials in showing how Eliot's personal voice works through the sordid, the bawdy, the blasphemous, and the horrific to create a unique moral world and the only theory of moral criticism in English literature. The book also erodes conventional attitudes toward Eliot's intellectual and spiritual development, showing how early and consistently his classical and religious sensibility manifests itself in his poetry and criticism. The book examines his reading, his teaching, his bawdy poems, and his life-long attraction.